Pre-assembled ECMO: Enhancing efficiency and reducing stress in refractory cardiac arrest care - Tharusan Thevathasan; Sonia Lech; Andreas Diefenbach; Elisa Bechthold; Tim Gaßmann; Sebastian Fester; Georg Girke; Wulf Knie; Benjamin T. Lukusa; Sebastian Kühn; Steffen Desch; Ulf Landmesser; et al. (Resuscitation Plus)
Aim: Extracorporeal cardiopulmonary resuscitation (ECPR) by veno-arterial extracorporeal membrane oxygenation (VA-ECMO) during refractory cardiac arrest presents significant medical and psychological challenges for healthcare providers. Beyond managing cardiac arrest and preparing for potential coronary angiography, the ECMO circuit must be assembled and primed under strictly sterile conditions, contributing to additional psychological stress and potential delays in ECMO cannulation. This pragmatic study thought to evaluate whether pre-assembled and pre-primed ECMO circuits (pre-primed group) maintain sterility over a 21-day period, expedite ECMO initiation in ECPR patients and alleviate the psychological burden on the ECPR team, compared to newly assembled and primed ECMO circuits (on-demand group). Methods: In a prospective manner, ECMO circuits were either pre-assembled and pre-primed under sterile conditions, maintained for 21 days with culture samples taken every seventh day, or newly assembled and primed during the acute emergency situation. The transition from on-demand assembly and priming of ECMO circuits to pre-primed ECMO circuits occurred on January 1st, 2021. The interval between patients’ arrival in the cardiac catheterization laboratory and the initiation of ECMO was recorded and retrospectively compared between the two treatment groups. The ECPR team, comprising experienced cardiologists and nurses, was prospectively surveyed using the modified Perceived Stress Questionnaire (PSQ-20). Results: All aseptically pre-assembled and pre-primed ECMO circuits demonstrated sterile cultures for aerobic and anaerobic microorganisms as well as fungal agents over the 21-day period: 0/120 positive cultures (0 %, 95 % CI for binomial probability 0–0.03). The time to ECMO initiation was significantly reduced in the pre-primed group compared to the on-demand group: 13 [IQR 9–17] versus 31 [IQR 27–44] minutes, P < 0.001. Responses from ECPR physicians and nurses on the PSQ-20 were similar across all items. With the use of pre-primed ECMO circuits, all ECPR professionals reported a greater sense of settled inner feeling, considerably less psychological tension, fewer worries and insecurities, as well as more effective ICU shifts with improved personal goal achievement. However, treating ECPR patients with pre-primed ECMO circuits did not lead to increased job satisfaction or higher physical energy levels. Conclusion: Aseptically pre-assembled and pre-primed ECMO circuits maintain sterility for multiple weeks, significantly reducing ECMO initiation times and alleviating psychological strain on the ECPR team. Consequently, implementing these circuits in ECPR centers could enhance both patient outcomes and healthcare provider well-being.